2022
DOI: 10.1093/hmg/ddac226
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of homozygous ALDH18A1 variants reveals alterations in amino acid and antioxidant metabolism

Abstract: Mono- and biallelic variants in ALDH18A1 cause a spectrum of human disorders associated with cutaneous and neurological findings that overlap with both cutis laxa and spastic paraplegia. ALDH18A1 encodes the bifunctional enzyme pyrroline-5-carboxylate synthetase (P5CS) that plays a role in the de novo biosynthesis of proline and ornithine. Here we characterize a previously unreported homozygous ALDH18A1 variant (p.Thr331Pro) in four affected probands from two unrelated families, and demonstrate broad-based alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…As expected, as a consequence of the gain-of-function of CLPX and PLP, their established target ALAS2 as a rate-limiting enzyme of porphyrin/heme biosynthesis in most tissues showed massive accumulation. Strong accumulation, dispersion, and co-migration with CLPX were also apparent for the PLPdependent enzyme OAT, and similar accumulation also concerned the enzyme ALDH18A1, as previously reported in global proteome profiles [56,96]. Both factors have connected pathway functions in the interconversion of amino acids such as proline, glutamate, and arginine.…”
Section: Co-migration Of Mtssu Monomeric Factors With Eral1 As Expect...supporting
confidence: 80%
“…As expected, as a consequence of the gain-of-function of CLPX and PLP, their established target ALAS2 as a rate-limiting enzyme of porphyrin/heme biosynthesis in most tissues showed massive accumulation. Strong accumulation, dispersion, and co-migration with CLPX were also apparent for the PLPdependent enzyme OAT, and similar accumulation also concerned the enzyme ALDH18A1, as previously reported in global proteome profiles [56,96]. Both factors have connected pathway functions in the interconversion of amino acids such as proline, glutamate, and arginine.…”
Section: Co-migration Of Mtssu Monomeric Factors With Eral1 As Expect...supporting
confidence: 80%
“…As expected consequence of the gain-of-function of CLPX and the PLP, their established target ALAS2 as ratelimiting enzyme of porphyrin/heme biosynthesis in most tissues showed massive accumulation. Strong accumulation, dispersion and comigration with CLPX was apparent also for the PLP-dependent enzyme OAT, and similar accumulation concerned also the enzyme ALDH18A1, as previously reported in global proteome profiles [56,104]. Both factors play connected pathway functions in the interconversion of amino acids such as proline, glutamate and arginine.…”
Section: Comigration Of Mtssu Monomeric Factors With Eral1 As Expecte...supporting
confidence: 81%
“…The most important roles it plays are catalyzing the reduction conversion and coupled phosphorylation and synthesizing proline from glutamate (Guo et al, 2020;Kalmar et al, 2021;Pickwick et al, 2022). Furthermore, a recent study conducting a functional assessment of homozygous P5CS variants revealed alterations in amino acid and antioxidant metabolism (Colonna et al, 2023), which further supported the important role of P5CS in regulating the antioxidant system. Interestingly, derangements of amino acids in cachectic skeletal muscle such as significantly reduced quantities of glutamate were observed in both cancer cachexia animals as well as human cancer cachexia patients (Kunzke et al, 2020).…”
Section: Discussionmentioning
confidence: 79%
“…P5CS (Aldh18a1) is linked to antioxidant function and amino acid metabolism. The P5CS (Aldh18a1) regulates glutamate replenishment, which affects the metabolism of glutamine and glutathione (Colonna et al, 2023). When glutamate-cysteine ligase is overused, it can result in a glutamate shortage, which interference the synthesis of amino acids, including ornithine and proline.…”
Section: Introductionmentioning
confidence: 99%